Full-scale shaking table test for examination of safety and functionality of base-isolated medical facilities. - Sato, Eiji (Earthquake engineering & structural dynamics.)
A series of full scale shaking table tests are conducted using the E-Defense shaking table facility on a base isolated four story RC hospital structure. A variety of furniture items, medical appliances, and service utilities are placed on the hospital specimen in as realistic a manner as possible. Four ground motions are adopted, including recorded near fault ground motions and synthesized long period, long duration ground motions. The test results show that the base isolated system performed very effectively against near fault ground motions due to significant reduction in the floor acceleration response, and operability and functionability of the hospital service is improved significantly as compared with the case observed for the corresponding base-fixed system. Against the long period ground motion, however, the hospital service is difficult to maintain, primarily because of the significant motion of furniture items and medical appliances supported by casters. Resonance accentuated large displacements and velocities on the floors of the base isolated system, which causes such furniture items and medical appliances to slide, sometimes more than 3 m, resulting in occasional collision with other furnitures or against the surrounding partition walls. It is notable that a key to maintaining the function of the medical facilities is to securely lock the casters of furniture and medical appliances.